Emerging regenerative strategies for spinal cord injury: exosome-derived mechanisms and therapeutic insights - Fan, Haixia; Gao, Jie; Chen, Qian; Sun, Shuangshuang; Guo, Jinshen; Liu, Xiaodong; Li, Jinhu (Frontiers in Neuroscience, 2025)
BackgroundSpinal cord injury (SCI) often leads to severe motor and sensory impairments, and current treatment methods have not achieved complete neural repair. In recent years, exosomes have become a research focus in the treatment of nerve injuries due to their important roles in intercellular information transfer, immune regulation, and neural repair. Our study conducts a scientometric analysis to map the research landscape related to exosomes in SCI.MethodsArticles and reviews related to exosome in SCI were retrieved from the Web of Science Core Collection and Scopus. Analysis was conducted using Microsoft Excel 2021, CiteSpace (6.4.R1), VOSviewer (1.6.18), the R software (4.4.3) bibliometrix package, etc.,ResultsSince 2018, the number of publications has rapidly increased. Fan Jin is the most academically influential author in the field, while Cai Weihua’s research has received widespread recognition from researchers. China is the leading contributor among the 32 countries/regions. Among the 708 institutions, Central South University and Zhejiang University are the primary supporters. Journal of Nanobiotechnology is the most influential journal in this field, with Neural Regeneration Research and Cells also making significant contributions. Keyword analysis focuses on “mesenchymal stem cells,” “inflammation,” “cell therapy,” “axonal regeneration,” “functional recovery,” “neuroinflammation,” “neurodegeneration,” “ferroptosis,” “pyroptosis,” and “precision medicine” emphasizing cellular therapies for tissue repair. Emerging topics like “nanoparticles” show significant potential in SCI treatment, further enhancing regenerative medicine approaches.ConclusionOur study show that the growing global interest in exosome-based therapies for SCI, marking an important step in understanding their preclinical potential. These therapies show promise in promoting neuroprotection, axonal regeneration, and modulating inflammation. Moving forward, future research will focus on further exploring the integration of exosome therapies with advanced drug delivery systems and regenerative medicine, aiming to enhance SCI treatments and tailor recovery strategies in preclinical models.